VESTIBULAR DYSFUNCTION AND BALANCE IMPAIRMENT IN HEAD AND NECK CANCER PATIENTS UNDERGOING CHEMOTHERAPY : A SYSTEMATIC REVIEW AND META-ANALYSIS - Novita, Khuznita Dasa (International Journal of Health Science & Medical Research, 2026)
Vestibular dysfunction is an important yet underrecognized adverse effect among patients with head and neck cancer (HNC) receiving platinum-based chemotherapy. Although cochlear toxicity is well documented, evidence specifically addressing vestibular impairment in this population remains limited and methodologically variable. The novelty of this study lies in presenting the first systematic review and meta-analysis exclusively examining vestibular dysfunction in adult HNC patients receiving chemotherapy, thus establishing a more focused and consolidated evidence base. To quantify the pooled incidence, clinical features, and diagnostic patterns of vestibular dysfunction in adults with HNC undergoing chemotherapy, and to identify chemotherapeutic agents strongly associated with vestibulotoxicity . Conducted in accordance with PRISMA 2020 guidelines and prospectively registered in PROSPERO (CRD420251080552), this review regularly searched Embase, Scopus, Web of Science, and the Cochrane Library for studies published between 2014 and 2024. Eligibility criteria included adult HNC patients treated with and reporting vestibular outcomes. Risk of bias was assessed using RoB 2.0 for randomized trials and the Newcastle–Ottawa Scale for observational studies. A random-effects model was applied for quantitative synthesis. Sixteen studies met the inclusion criteria, and contributed fourteen data to the meta-analysis. The pooled incidence of vestibular dysfunction was 24.7% (95% CI: 19.2–30.8). Dizziness and imbalance were the most frequently reported symptoms, while peripheral vestibular deficits were confirmed through vHIT , VEMP, and caloric testing. Cisplatin was consistently identified as the principal chemotherapeutic agent associated with vestibulotoxicity. These findings underscore the need for standardized vestibular assessment and routine monitoring, particularly within cisplatin-based treatment regimens.